1996
DOI: 10.1111/j.1540-8167.1996.tb00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Findings Following Slow Pathway Ablation for AV Nodal Reentrant Tachycardia

Abstract: Ablation of the slow pathway to cure AV nodal reentrant tachycardia does not produce any gross or histologic damage to the AV node, suggesting that the AV nodal reentrant circuit does not exist in its entirety in the AV node.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As far as we are aware, two case reports exist 24,25 that provide a histological description of the site of slow pathway ablation, each in a patient with clinically successful ablation. In both instances, the site of ablation was readily identified and localized posterior to the AV node.…”
Section: Study Limitationsmentioning
confidence: 99%
“…As far as we are aware, two case reports exist 24,25 that provide a histological description of the site of slow pathway ablation, each in a patient with clinically successful ablation. In both instances, the site of ablation was readily identified and localized posterior to the AV node.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Histological findings in patients also have provided evidence that the AV node itself does not participate in the slow pathway conduction. 17,18 These findings strongly suggest that the tissue inferior to the compact AV node is used in the reentry circuit of the AVNRT.…”
Section: Discussionmentioning
confidence: 90%
“…However, the ablation lesions of the slow pathway were found to be in the atrial myocardium in the cases in which histology was done. 17,18 Thus, it remains debatable whether or not the destruction of the inferior extension of the AV node is required for the cure of AVNRT. Meanwhile, other substrates for the slow pathway have been suggested.…”
Section: Tachycardia Circuit In Avnrtmentioning
confidence: 99%
“…Anterior 4,5 or left‐sided 6 approaches are rarely indicated. Pathologic data showed that ablation of the slow pathway to cure AVNRT does not produce any gross or histologic damage to the compact AV node, suggesting that the AV nodal reentrant circuit does not exist in its entirety in the compact AV node and is composed in part from the subatrial approaches to the AV node distinct from the compact AV node 7,8 . Anatomically based targeting of the “slow pathway region” with radiofrequency catheter ablation therapy has been considered the definitively safe and effective therapy of choice for the majority of patients.…”
Section: Editorial Commentmentioning
confidence: 99%